MWCNTs-Fe3O4 nanocomposite for Hg(II) high adsorption efficiency - Sadegh, Hamidreza; Ali, Gomaa A. M.; Makhlouf, Abdel Salam Hamdy; K. F., Chong; Alharbi, Njud S.; Agarwal, Shilpi; Gupta, Vinod Kumar (Elsevier, 2018)
Magnetic carbon nanotubes composite (MWCNTs-Fe3O4) was successfully prepared and characterized using different techniques. MWCNTs-Fe3O4 displays entangled network of oxidized MWCNTs attached with Fe3O4 clusters with specific surface area of 92 m2 g−1. The adsorption performance of as prepared composite was investigated for Hg(II) removal. Several experimental factors affecting Hg(II) adsorption process by MWCNTs-Fe3O4 were studied including, adsorbent dosage, contact time, pH and metal ion concentration. A high adsorption capacity of 238.78 mg g−1 was obtained according to Langmuir model. In addition, pseudo-second-order and the Langmuir isotherm model were used to fit the adsorption kinetic and equilibrium data, respectively. The results recommend the successful application of MWCNTs-Fe3O4 for Hg(II) removal via batch adsorption technique.